Desenvolvimento de procedimentos para a determinação de cobre e zinco em fertilizantes minerais misto por espectrometria de emissão óptica com plasma induzido por micro-ondas (MIP OES) - Fidelis, Suzane Cristina (Universidade Federal de São Carlos, 2022)
DEVELOPMENT OF PROCEDURES FOR COPPER AND ZINC DETERMINATION IN MIXED MINERAL FERTILIZERS BY MICROWAVE-INDUCED PLASMA OPTICAL EMISSION SPECTROMETRY (MIP OES). In the pulp industry, eucalyptus, introduced in Brazil in 1904, is the main raw material, according to the Brazilian Association of Silviculture. For these plants' good development, fertilizers must be used to meet their nutritional needs. In this approach, the determination of nutrients both in plants and in fertilizers is a demand of industrial quality control laboratories. Mixed mineral fertilizers, specifically the micronutrients copper and zinc, were the object of the present study. In partnership with the raw material supplier, aspects related to sampling were evaluated, and compaction during transport was investigated. Next has studied the sample preparation, with digestions involving open vials and assisted by microwave radiation. The determination of the analytes (copper and zinc) was performed by microwave-induced plasma optical emission spectrometry (MIP OES). The equipment and materials necessary for the execution of this project were made available in the laboratories of Bracell, unit in Lençóis Paulista, in the São Paulo State. The raw material responsible for being the source of copper and zinc (10% of each nutrient) was provided by the supplier. Different extractor solutions such as aqua regia, sulfuric acid, and citric acid did not show greater extractions effectiveness than hydrochloric acid, the method recommended by the manual of analytical methods of the Braziliam Ministry of Agriculture, Livestock and Food Supply (MAPA). The wet digestion procedure in an open system on a hot plate presented statistically similar mean values (paired t-test) compared to the digestion performed in a closed system in a microwave digester for Cu. Otherwise, for Zn, the digestion assisted by microwave radiation was less effective, which suggested problems related to the heater program. The matrix after grinding (20 mesh) and the intermediate portion (retained in a sieve) were analyzed. Addition and recovery tests showed high recovery levels in part had on the sieve in all extractor studied solutions. The results suggest a possible matrix effect in MIP OES determinations, indicating the need to evaluate new alternatives for calibration or the use of an internal standard.
Development of procedures for the determination of copper and zinc in mixed mineral fertilizers by optical emission spectrometry with microwave-induced plasma (MIP OES)
Keywords: Fertilizante; MIP-OES; Celulose; Cobre; Zinco; Micronutriente; Método; Indústria; Desenvolvimento; Espectrometria; Plasma; FAAS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA